Hydrokinesitherapy to treat motor sequelae in older adults with strokes. (RIAF. International Journal of Physical Activity, 2025)
The present research was determined by a mixed approach; its objective is to design a methodological strategy for physical-therapeutic care in motor sequelae produced by strokes in older adults, it proposes in its structure a distinctive theoretical-methodological guide of procedures and physical-therapeutic means for the implementation of exercises and body postures that are developed with the use of seawater in spas of coastal communities. The methodological work distinguishes an elementary function in prophylactic and therapeutic physical activity, with repercussions on the medical- pedagogical components that are developed in stages of the rehabilitation process. The selection and application of scientific research methods and techniques was in charge of theoretical, empirical and statistical mathematical levels, emphasizing non-participant observation, interviews, as well as processing with descriptive statistics. The methodological strategy is novel in nature considering the use of hydrotherapeutic techniques that make use of the benefits of the marine aquatic environment by relieving the hydrostatic, hydrodynamic and hydrokinetic elements for physical rehabilitation in sequelae produced by strokes in older adults. The functionality of the proposal was established by the expert criterion method, which allowed the evaluations witnessed to be assumed in order to validate their effectiveness. The conclusions of the study were directed through the construction of the methodological strategy for the preparation of Physical Culture professionals in order to use hydrosynetiotherapy for the motor sequelae produced by cerebrovascular accidents in older adults.
Keywords: Hydrokinesitherapy; Stroke; Adult Elders